2020
DOI: 10.20343/teachlearninqu.8.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Does it Matter Where You Teach? Insights from a Quasi-Experimental Study on Student Engagement in an Active Learning Classroom

Abstract: Active learning has experienced a recent resurgence with the advent of specialized active learning classrooms. While the fundamental theory behind active learning is anything but new, a relatively recent finding is that active learning pedagogies thrive in suitable active learning classrooms. To date, studies of active learning have focused on outcomes such as student performance. The quasi-experimental study described in this article investigated self-ratings of student engagement as an outcome of active lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…A major shift that took place in terms of pedagogy was from traditional teachercentered approaches that made students passive learners to more student-centered approaches that promote active engagement in the learning process. Several recent studies have found that active classrooms significantly improve student engagement across various disciplines and grade levels [88][89][90][91]. The Vice Principal explained, "they (students) were learning like robots .…”
Section: Active Learning Pedagogymentioning
confidence: 99%
“…A major shift that took place in terms of pedagogy was from traditional teachercentered approaches that made students passive learners to more student-centered approaches that promote active engagement in the learning process. Several recent studies have found that active classrooms significantly improve student engagement across various disciplines and grade levels [88][89][90][91]. The Vice Principal explained, "they (students) were learning like robots .…”
Section: Active Learning Pedagogymentioning
confidence: 99%
“…It can be put into practice and applied as a process in which learners participate in developing thinking processes, analyzing, studying, researching, experimenting, and seeking knowledge by themselves (Bonwel & Eison, 1991) according to their aptitudes. Interest with a variety of processes and learning resources both inside and outside the classroom can bring knowledge and experiences to improve the quality of life of oneself, society, and the public (Ministry of Education 2018: [11][12][13][14]. Active learning is a process in which learners must take action (Bonwell & Jame, 1993; Holec & Marynowski, 2020; Karcher et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for pre-tenure faculty who have added concerns related to the promotion and tenure process (Wieman, Perkins, and Gilbert 2010). The transition to an active learning classroom environment may also be perceived as relinquishing control and more time consuming because instructors must prepare course activities (Holec and Marynowski 2020;Michael 2007).…”
Section: Introductionmentioning
confidence: 99%